2022
DOI: 10.1177/00034894221115754
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors Associated with Respiratory Compromise in Planned PICU Admissions Following Tonsillectomy

Abstract: Objectives: Review the incidence and factors associated with respiratory compromise requiring intensive care unit level interventions in children with planned admission to the pediatric intensive care unit (PICU) following tonsillectomy or adenotonsillectomy (T/AT). Study design: Retrospective cohort study. Methods: Review of all patients with PICU admissions following T/AT from 2015 to 2020 at a tertiary care pediatric hospital. Patient demographics, underlying comorbidities, operative data, and respiratory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 17 publications
4
5
0
Order By: Relevance
“…Some of the most cited risk factors include age younger than 2-3 years old, severe OSA, craniofacial abnormalities, extremes of weight, black race, and cardiac, pulmonary, or neuromuscular diseases. [1][2][3][4][6][7][8]16,17 However, similar to our findings, respiratory compromise is unlikely even among these high-risk patients. [2][3][4][5][6][7][8][9][10] Previous studies suggested that most postoperative respiratory complications occur within a few hours of surgery.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Some of the most cited risk factors include age younger than 2-3 years old, severe OSA, craniofacial abnormalities, extremes of weight, black race, and cardiac, pulmonary, or neuromuscular diseases. [1][2][3][4][6][7][8]16,17 However, similar to our findings, respiratory compromise is unlikely even among these high-risk patients. [2][3][4][5][6][7][8][9][10] Previous studies suggested that most postoperative respiratory complications occur within a few hours of surgery.…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3][4][6][7][8]16,17 However, similar to our findings, respiratory compromise is unlikely even among these high-risk patients. [2][3][4][5][6][7][8][9][10] Previous studies suggested that most postoperative respiratory complications occur within a few hours of surgery. 3,8,13 Friedman et al conducted a prospective study aimed at identifying high-risk patients who require overnight admission after T/AT, and proposed that a child with no known preexisting oxygen requirements who is off oxygen 3 h after surgery can be safely discharged home regardless of baseline comorbidities and severity of AHI.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations